Procrastination, well-being, and academic performance among pre-service teachers in blended learning modality - Laureles, Dann Aibrielle D. (Institut Agama Islam Negeri Langsa, 2024)
The purpose of the study is to know how pre-service teachers are impacted by procrastination, and how it influences their well-being and academic performance in a blended learning modality. The study used a quantitative approach particularly the descriptive-correlation. The participants were gathered using random sampling. There were a total of 224 students who answered the online survey through Google Forms, but it was found that 32 students did not provide some information that was needed, so the final number of students was 192. The findings show that academic procrastination and academic performance are positively correlated, and there is a significant but very weak relationship between the two variables (r(190) = .143, p = .48). The researcher also found that there is no correlation between well-being and academic performance (r(190) = -.037, p = .612). Lastly, it also shows another significant finding in which procrastination and well-being have a significant correlation (r(190) = -.0328, p = .001). There is a significant but weak relationship between the two variables, and it is negatively correlated. Because said, the more that academic procrastination increases, there is an 11% chance that the well-being of a student will decrease.